Empirical analysis on influencing factors of waste paper recovery rate in China. (2nd April 2016) - Gang, Diao; Bao-dong, Cheng; Si-Tong, Liu; Yu, Rong
ABSTRACT: The research calculated the waste paper recovery rate, and analyzed the main factors influencing waste paper recovery rate in China with time series data from 1970 to 2012. The consequent recovery rate and utilization rate of waste paper show that the recovery of paper products has been experiencing a rapid growth in China, but it cannot meet the domestic need. The empirical analysis proves that demand is the main driver to stimulate the increase of waste paper recovery rate in China; the increased average GDP per capita and proportion of waste paper pulp are two other important factors; the increased urbanization rate does not exert significant influence. In the circumstance of insufficient timber supply, the policy of eliminating straw pulp capacities for paper-making indusrty improves the recovery rate of waste paper.